Participatory design & health information technology - Kanstrup, A. M.; Bygholm, Ann; Bertelsen, Pernille; Nøhr, Christian (Studies in health technology and informatics, 2017)
Health Information Technology (HIT) continues to increase in importance as a component of healthcare provision, but designing HIT is complex. The creation of cooperative learning processes for future HIT users is not a simple task. The importance of engaging end users such as health professionals, patients and relatives in the design process is widely acknowledged, and Participatory Design (PD) is the primary discipline for directly involving people in the technological design process